FAO fisheries technical paper N.350.2: Precautionary approach to fisheries: Part 2 - FAO FAO (FAO, 1996)
It contains a series of scientific papers prepared to provide a comprehensive review and analytical background for the drafting of guidelines on the precautionary approach to fisheries. It provides a comprehensive review of the concept of precaution in all aspects of fisheries and of its implication for fishery research, technology development and transfer, as well as for conservation and management. It also provides with a series of tropical papers on: (a)the development of scientific advice with incomplete information; (b) risk assessment, economic and precautionary fishery management; (c) precautionary management reference points and management strategies; (d) the assessment of the precautionary nature of fishery management atrategies; (e) the precautionary approach to species introduction; and (f) the precautionary aspects of fishery technology development.